Pengaruh Model Pembelajaran Problem Based Learning Berbasis Kemampuan Berpikir Kritis Peserta Didik Kelas V Pada Hasil Belajar Mata Pelajaran IPAS SD N Tugu Jebres Surakarta Tahun Pelajaran 2023/2024 - Zulaema Tiara Rahman; Oktiana Handini; Sarafuddin Sarafuddin (Journal on Education, 2024)
The purpose of this study was to determine the effect of problem-based learning model based on critical thinking skills of fifth grade students on the learning outcomes of IPAS SD N Tugu Jebres Surakarta in the 2023/2024 academic year. This study used a quantitative method with a one group pretest-posttest design. Data analysis techniques in this study used normality test, homogeneity test and paired sample t-test. The results of data analysis of pretest results obtained an average of 59.75 while the posttest obtained an average of 89.4 when viewed from the average pretet and posttest experienced an increase. The results of data analysis with the paired sample t-test test obtained tcount = 12.112 can be compared with the ttable value using dk = (N-1) then (20-1) = (19) with a level at 5% or 0.05 significance so, tcount> ttable = 12.112> 2.093 then, the results show H0 is rejected and Ha is accepted. Based on the significance value, the result is 0.000 where, 0.000 <0.05 so that the result shows H0 is rejected and Ha is accepted. From the results of data analysis, the hypothesis states that there is an influence of the problem-based learning model based on the critical thinking skills of fifth grade students on the learning outcomes of IPAS subjects at SD N Tugu Jebres Surakarta in the 2023/2024 school year.